Cup quality profiles of Robusta coffee wilt disease resistant varieties grown in three agro‐ecologies in Uganda. (16th August 2021) - Mulindwa, Joseph; Kaaya, Archileo N; Muganga, Lawrence; Paga, Moses; Musoli, Pascal; Sseremba, Godfrey; Wagoire, William W; Bitalo, Daphne N
Abstract: BACKGROUND: The recently developed Robusta coffee wilt disease resistant (CWD‐r) varieties in Uganda outperform the local landraces, both in yield and resilience. However, their uptake has been slow due to limited information on their cup worth. This study profiled the cup worth of the five most commonly grown CWD‐r across the Lake Victoria Crescent, Western Mid‐altitude farmland and Central Wooded Savannah agro‐ecologies. RESULTS: Significant correlations ( P ≤ 0.05) were observed between soil nutrients and coffee bean size but this was not the case for biochemical and cup quality. The proportion of coffee beans retained on screen 15; minimum acceptable size through coffee commercial markets, ranged from 58.09% in Mukono to 92.49% in Mityana. Interestingly, the bean size of variety KR4 was hardly influenced by environmental variations, with portions of beans retained on screen 15 being relatively the same (80.30% Ibanda, 89.50% Mukono, 98.20% Mityana). Coffee cup quality for most of the varieties was scored as premium (70–79%) across three agro‐ecologies, with the exception of KR4, which was scored specialty grade (≥80%). Coffee blends generated were used to make coffee products with specialty score (82.25%) and a distinctive aroma complex. CONCLUSION: In this study, blends of CWD‐r resulted in superior cup scores (76–82%). These findings show that CWD‐r varieties have a high cup worth with potential for wide adaptation in Uganda's Robusta coffee growing agro‐ecologies. Most importantly, variety KR4 has resilience across three agro‐ecologies with a consistent high bean size and superior cup quality, making it a candidate variety for the market and breeding. © 2021 Society of Chemical Industry.